Evaluating the use of meropenem in hematologic patients with febrile neutropenia - R.A. Stuurman; E. Jong; P.C.R. Godschalk; M.F. Corsten; J.E. Nagtegaal (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract